2018
DOI: 10.1001/jamapsychiatry.2017.3828
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Parent-Offspring Resemblance for Major Depression in a National Swedish Extended Adoption Study

Abstract: The parent-offspring resemblance for treated MD arises from genetic factors and rearing experiences to an approximately equal extent. Both forms of cross-generational transmission act additively on the risk for MD in the offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 40 publications
(91 reference statements)
3
38
2
Order By: Relevance
“…When adjusting for parental propensity scores, the transmission of psychopathology did not entirely explain the Table 4 Hazard rate of suicidal behavior in the offspring generation among offspring exposed to parental suicidal behavior in different comparison groups. transmission of suicidal behavior, which is consistent with both our Cox proportional hazard results and previous literature examining the intergenerational transmission of anxiety, neuroticism, and depression 21,[51][52][53][54][55][56] . The remaining environmental mediation suggests that having a parent who displayed suicidal behavior may confer an increased risk for offspring suicidal behavior through mechanisms such as contagion [5][6][7][8][9] , bereavement after parental loss [10][11][12] , negative parenting style (e.g., hostility) 22,57 , or chaotic home environment [13][14][15] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When adjusting for parental propensity scores, the transmission of psychopathology did not entirely explain the Table 4 Hazard rate of suicidal behavior in the offspring generation among offspring exposed to parental suicidal behavior in different comparison groups. transmission of suicidal behavior, which is consistent with both our Cox proportional hazard results and previous literature examining the intergenerational transmission of anxiety, neuroticism, and depression 21,[51][52][53][54][55][56] . The remaining environmental mediation suggests that having a parent who displayed suicidal behavior may confer an increased risk for offspring suicidal behavior through mechanisms such as contagion [5][6][7][8][9] , bereavement after parental loss [10][11][12] , negative parenting style (e.g., hostility) 22,57 , or chaotic home environment [13][14][15] .…”
Section: Discussionsupporting
confidence: 92%
“…However, the use of the quantitative behavior genetic analyses used a different scale for association (i.e., tetrachoric correlations) and was similar on this scale. Second, the offspringof-siblings design is unable to adjust for environmental factors unique to each nuclear family 55 and address assumptions related to assortative mating 64 . We included both maternal and paternal measured covariates to limit this bias, but we cannot make a definitive causal inference.…”
Section: Discussionmentioning
confidence: 99%
“…As expected given this pattern, we found modest evidence for shared environmental effects for both men and women in our sibling analyses. These findings are consistent with our recent results from an extended adoption study of major depression in Sweden (35), which found significant correlations between major depression in adoptive and stepparents and their nonbiological children.…”
Section: Estimation Of Heritability In Twin Studiessupporting
confidence: 93%
“…Notably, of the five affective temperaments, cyclothymic, and hyperthymic temperaments were both significantly and positively associated with recent life event exposure. Our results add to the long debate and ever-expanding research focusing on the relative role of nature or nurture, that is, biological or environmental contributors in the development and severity of depression (26). Although genetic approaches including both candidate gene and GWAS studies generally fail to provide replicable and conclusive results (14,27), temperaments, which develop on a strong genetic and biological basis (28), influence neuroendocrine and autonomic processes (29) and determine emotional and behavioral reactivity with an early manifestation and strong temporal stability, have been repeatedly shown to be associated with depression (30)(31)(32).…”
Section: Discussionmentioning
confidence: 57%